A Human Capital Index for the Italian Provinces - Alessandra Pasquini; Furio C. Rosati (Institute of Labor Economics (IZA), 2020)
Good health conditions and high quality education are crucial for children development and for their future contribution to the society. Human capital has been recognized as one of the crucial engines of economic growth. Nonetheless, it is often hard to establish a metric that allows to monitor its evolution and contribute to assess the effects of policies. In Italy, the use of such an index at national level may not be enough to have a clear picture of the human capital conditions. Socio-economic characteristics and public services are highly heterogeneous across the Country. There is, therefore, good ground to believe that also the human capital presents substantial differences across the Italian Provinces. To take such a high heterogeneity into consideration, we develop a Human Capital Index for Italy disaggregated at provincial level. The results show very large differences across Italian Provinces in terms of human capital, mostly driven by the variation in the quality of educational. Strikingly, the differences among Italian Provinces span a range that goes from best performers among high income countries to middle and low income countries. Finally, we classify the Italian Provinces in three main clusters according to their HCI and show how the clusters differ in terms of several socio-economic characteristics.
Keywords: I20; I24; I28; 330; human capital; index; Italian provinces